Agonistic Association of Lepidoptera and Fungus in the Development of Leaf-spot Disease in High Altitude Mango and its Control - Saha, Priyanka Lahiri, Ishita Mukherjee, Ayantika Bhattacharya, Arup Kumar Mitra*, Pip Banerjee, Gaurav (Journal of Phytology, 2010)
Plants are common prey for pests, though plants at high altitudes are less prone to diseases. However, our sample proved to be an exception, as disease in plants have become a major problem in North India, especially in old, crowded orchards where there is excessive shade .Mango, our test plant, is well adapted to tropical and subtropical climate. Here we considered the mechanism of disease initiation in the mango leaves by the entry of a fungal pathogen- Cercospora mangiferae, and its possible agonistic association with an insect of the Lepidoptera group, Procontarinia sp . Our aim is to suggest a pesticide to avert the entry and reduce the occurrence of the disease. The specimen, collected from a place called Jorolle (NH 88) near Sundernagar, is 10 kms away from the Beas-Sutlej confluence in the state of Himachal Pradesh, during the months of January-February, the temperature recorded was between 7-14Â°C. The environment in the vicinity of the mango orchard was dry, windy, and grimy and plagued by vehicular emissions. There were predominantly 2 kinds of leaf spots-a white and a brown spot. The spread of the disease started from the lower mature leaves to the upper younger leaves. Enormity of the infection was much greater in leaves having galls along their margins. The gall formation results due to the mechanical damage caused by the infection due to a midge fly (Procontarinia sp). The average diameter of galls ranged between 3-4mm. As affirmed earlier, the leaves with large number of galls are the primaryÂ home for the fungus- Cercospora mangiferae where they reside in larger numbers. Although the mechanism of an agonistic association is obscure but the possibility of such an association cannot be ruled out completely; where the primary infection caused by the midge insect paves the way for secondary infection by the fungus. Our sole intention was to prevent occurrence of such an association, by inhibiting both the infections from occurring individually. Our test pesticide belonged to the Malathione group. Its main component is monocrotophos which interferes not only with the nerve impulse transmission of the insect but also damages the cell wall of the fungal pathogen thereby attending both the problems. The experiment was performed with different concentrations of pesticide and it was observed that at 43.5%w/w it was effective enough to prevent 100% germination. Our studies provide a conclusive result which suggests that if the pesticide, at the effective concentration is sprayed till run-off, the young tender leaves of Mangifera indica will be protected from both the midge insect as well as the fungal pathogen. Key words: Chausa, Langra, Dashehari, Leaf spot, Cercospora mangiferae, White spot, Brown Spot, Gall, Procontarinia sp., pesticide, Malathione, Hilcron, Monocrotophos <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Arup Kumar Mitra et al. Agonistic Association of Lepidoptera and Fungus in the Development of Leaf-spot Disease in High Altitude Mango and its Control. Â J Phytol 2/7 (2010) 28-36.